The vanishing Cherry Blossom Bookshop - Asakura, Takuya, 1966- (HarperCollinsPublishers, 2025)
Welcome to The Cherry Blossom Bookshop, a haven for book lovers that only appears during the fleeting cherry blossom season. Nestled amidst the bloom of delicate petals, you'll find a sanctuary for those burdened by regrets and past sorrows. Here, Sakura, the mysterious young owner, and her wise calico cat, Kobako, patiently await the arrival of souls in need of solace and healing. Told over four seasons, each visitor to the bookshop holds a book that bridges their past and present, guiding them towards understanding and acceptance. Within the antique charm of the shop and the soothing aroma of freshly brewed coffee, Sakura and Kobako help their guests confront their lingering sadness through the power of stories, enabling them to move forward with renewed hope.